СУЧАСНІ АСПЕКТИ ВИКОНАННЯ МАСТЕКТОМІЇ (World Science, 2019)
We have proposed performing zigzag-like access when performing mastectomy. The use of the proposed access in patients of the main group relative to the comparison group allowed to reduce the retention time of postoperative drainage by 5,96 days, educe the time of use of parenteral analgesic therapy by 5,33 days, reduce the inconsistency of postoperative wounds by 10,4%, reduce the incidence of gray by 7,6%.